Domestic Road Infrastructure and International Trade: Evidence from Turkey - A. Kerem Coşar; Banu Demir (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Poor domestic transportation infrastructure in developing countries is often cited as an important impediment for accessing international markets. Yet, evidence on how transportation infrastructure improvements affect the volume and composition of exports is scarce. Drawing on the large-scale public investment in expressways undertaken in Turkey during the 2000s, this paper contributes to our understanding of how internal trade costs affect regional exports and specialization. Two results emerge. First, we estimate that this road infrastructure project accounts for 15 percent of the export increase from interior regions, generating a 10-year discounted stream of additional export revenues that amount to between 9 and 14 percent of the value of the investment. Second, while the exports of all industries within a given region increase in response to improvements in connectivity to the international gateways of the country, the magnitude of this increase is larger the more time sensitive an industry is. Accordingly, we also observe an increase in the regional employment and revenue shares of such industries. Our results support the hypothesis that internal trade costs can be a determinant of international specialization and comparative advantage.
Keywords: F14; R11; R41; 330; international trade; infrastructure; transportation costs; time-sensitive industries